Cavernous Malformation of the Optic Nerve and Chiasm: Prompt Suspicion and Surgery Matter. Issue 1 (March 2022) - Kostic, Maja; Subramanian, Prem S.; Falcone, Steven F.; El-Swaify, Seif Tarek; Sur, Samir; Spasic, Smiljana; Miller, Neil R.; Morcos, Jacques J.; Lam, Byron L.
Abstract : Background: Cavernous malformations (CMs) of the optic nerve and chiasm are extremely rare, accounting for less than 1% of all intracranial CMs. Acute, subacute, or progressive visual loss from CM may occur with or without hemorrhage. Prompt surgical excision of the CM offers the best hope to improve or stabilize vision. Given its rarity, optic nerve and chiasm CMs may not be readily suspected. We provide 3 cases of optic nerve and chiasm CM, highlighting key neuroimaging features and the importance of expedited intervention. Methods: Case records of the neuro-ophthalmology clinics of the Bascom Palmer Eye Institute and the University of Colorado, and literature review of reported cases of optic CM. Results: A 49-year-old woman reported acute progressive painless vision loss in the right eye. MRI showed a suprasellar mass with heterogeneity in signal involving the right prechiasmatic optic nerve. Surgical excision of the CM 5 days after onset of visual loss improved vision from 20/300 to 20/30. A 29-year-old woman with acute painless blurred vision in the right eye had anterior chiasmal junctional visual field defects corresponding to a heterogeneously minimally enhancing mass with blood products enlarging the optic chiasm and proximal right optic nerve. Surgical excision of the CM 8 weeks after onset of visual loss improved vision from 20/40 to 20/15 with improved visual fields. A 33-year-old woman with a history of familial multiple CMs, diagnosed at age 18, reported new-onset severe headache followed by blurred vision. MRI showed a hemorrhagic lesion of the optic chiasm and right optic tract. She was 20/20 in each eye with a reported left superior homonymous hemianopia. No intervention was recommended. Vision of the right eye worsened to 20/400 2 months later. The patient was followed over 13 years, and the MRI and visual function remained unchanged. Literature review yielded 87 optic CM cases occurring across gender and nearly all ages with visual loss and headache as the most common presenting symptoms. Optic chiasm is the most common site of involvement (79%). Nearly 95% of reported CM cases were treated with surgery with 81% with improved vision and 1% with worsened vision. Conclusion: MRI features are critical to the diagnosis of optic nerve and chiasm CM and may mimic other lesions. A high index of suspicion by the neuro-ophthalmologist and neuroradiologist leads to early recognition and intervention. Given optic CM displaces and does not infiltrate neural tissue, expedited surgical resection by a neurosurgeon after consideration of other diagnostic possibilities improves visual function in most cases. Abstract : Supplemental Digital Content is Available in the Text.